Stock Index Futures and Hedging Performance: Evidence from Developed and Emerging Markets - Zhang, Shu (2007)
The primary function of stock index futures is to allow investors to hedge their spot equity portfolios. And hedging effectiveness can be a criterion of success of index futures contract. This research attempts to evaluate the hedging performance of stock index futures in developed and emerging markets and find some further implications for developing stock index futures in emerging markets.